Alanna : the first adventure - Pierce, Tamora; OverDrive, Inc. (New York : Atheneum Books for Young Readers, 2002)
Eleven-year-old Alanna, who aspires to be a knight even though she is a girl, disguises herself as a boy to become a royal page, a learning many hard lessons along her path to high adventure.
"An Argo book."
Electronic audio file.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Alanna (Fictitious character : Pierce) -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Sex role -- Juvenile fiction; Knights and knighthood -- Fiction; Sex role -- Fiction; Electronic audio books